PARAMETERS OF THE ANTI-ROTOR HYDRO UNIT WITH DIFFERENT TYPES OF IMPELLER (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It is known that the main part of the existing rivers, canals and other hydro sources have a low pressure. Today, almost all over the world, the use of this hydropower potential for the purpose of generating electricity is of particular interest and is considered an urgent task [1].